REGIONAL BANKS AS A NECESSARY TOOL TO STIMULATE SOCIAL AND ECONOMIC DEVELOPMENT OF THE REGIONS OF UKRAINE - KOVALENKO, MYKOLA; PASEMKO, HALYNA; KOVALENKO, MYKOLA; NAKISKO, OLEKSANDR; RUDENKO, SERHII (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The role and importance of regional banks in stimulating the socio-economic development of the regions of Ukraine were investigated. The author’s vision of such definitions as regional banks and the regional banking system is offered. It is established that the regional banking system of Ukraine has undergone a significant reduction in recent years and has a very small share of assets, liabilities, and capital in the total banking system of the country. It is proved that the National Bank of Ukraine does not take into account the importance of having a regional banking system and ensuring the balanced socio-economic development of the regions of Ukraine. Examples of the organization of banking business of the USA and Germany are given. It is substantiated that regional banks can be full-fledged subjects of the modern banking system only with some support from the NBU and local authorities.